Individuals Receiving Specialized Treatment for Drug and Alcohol Dependence and Gambling Disorder in Israel—Characteristics and Implications for Prevalence Estimates. Issue 3 (July 2014) - Lev-Ran, Shaul; Florentin, Iris; Feingold, Daniel; Rehm, Jürgen
Background: Substance dependence is one of the main factors contributing to morbidity and mortality worldwide. Gambling disorder has recently been included as an addictive disorder in DSM-5 ( Diagnostic and Statistical Manual of Mental Disorders, 5th edition) and is associated with substantial psychiatric comorbidity and respective disability. Nevertheless, the vast majority of those suffering from these disorders do not receive treatment. In Israel, prevalence of substance dependence has traditionally been estimated to be lower than those in high-income countries, though prevalence estimates from the recent decade are lacking. Moreover, characteristics of individuals seeking treatment for substance dependence and gambling disorder have not been published. Methods: In this study, the authors analyzed data from the Israel National Addiction Registry, a computerized database that includes sociodemographic characteristics of all individuals treated in specialized public facilities for substance dependence and gambling disorders in the years 2003–2012. Results: The prevalence of treatment utilization for drug and alcohol dependence and gambling disorders were 0.2%, 0.1%, and 0.01%, respectively. These rates generally remained stable throughout the last decade. Individuals seeking treatment for alcohol dependence were in the lower socioeconomic status (SES) cluster, whereas those seeking treatment for drug dependence were in the midrange SES clusters, findings that are generally in concurrence with characteristics of treatment seekers in high-income countries. Conclusions: Prevalence estimates based on reports indicating that approximately 10% of individuals with substance dependence seek treatment suggest rates of alcohol dependence in Israel that are substantially higher those previously published, though still lower than most high-income countries. Nationwide epidemiologic studies exploring current rates of substance dependence and gambling disorder in Israel are urgently needed, and treatment options should be planned and funded accordingly. Potential reasons for these apparent low rates of treatment utilization for these disorders in Israel should be explored in order to improve services provided for this population.